Evaluasi Struktur dan Skala Upah Dengan Metode Adhered dan Overlapping UKM XY Sektor Kuliner Kota Bogor - Emi Ginawati; Hilyah Syahidah; Maulida Lutfia Aminin; Muhamad Arya Fadhillah (Universitas 45 Surabaya, 2024)
A vital function in human resource management is compensation. Compensation is an important aspect of human resource management and has a significant impact on job satisfaction, employee retention, and organizational success. Susu Mbok Darmi, which operates in the culinary sector and is located in the heart of Bogor City, is the focus of this research. This research aims to evaluate the employee compensation system of Susu Mbok Darmi to improve the effectiveness and efficiency of organizational productivity. In this study, a salary mapping method involving adhered and overlapping techniques was used. The research findings show that the overlapping technique is preferred to be applied in Susu Mbok Darmi Susu.